Journeys Home: A Longitudinal Study of Factors Affecting Housing Stability - Watson, N; Bevitt, A; Killackey, E; Johnson, G; Moschion, J; Scutella, R; Greer, N; Tseng, Y; Wooden, M; Chigavazira, A (My University, 2012)
As part of the Australian government’s commitment to halving the rate of homelessness by 2020, a research agenda was developed to expand the evidence base for understanding homelessness. A major component of this agenda was the commissioning of a new longitudinal study intended to track the experiences of a sample of persons currently facing housing difficulties, including persons with a recent history of homelessness,into the future(albeit,only over a relatively short period–two years). Work on the design of that study,now known as Journeys Home, commenced in late 2010, with the first wave of fieldwork conducted over the period, September to November 2011. This paper summarises the design of the study and reports on fieldwork outcomes from the first wave of data collection. It describes: the target population and approach to sampling from that population; surveycontent; and fieldwork parameters (e.g., survey mode, frequency,contact protocols, use of incentives). It also presents information on wave 1 response, including the characteristics of respondents and how they differ from non-respondents.
Keywords: Surveys and Survey Methodology; Housing,Affordability -- Stability; Homelessness; Surveys and Survey Methodology; Housing, communities and neighbourhoods; Surveys and survey methodology; Housing,Affordability; Surveys and Survey Methodology; Homelessness; Stability; Housing, communities and neighbourhoods; Surveys and Survey Methodology